Large-area semi-transparent light-sensitive nanocrystal skins - Akhavan, Shahab (2013)
Large area and semi-transparent highly light sensitive nanocrystal skin is demonstrated via spray-coating nanocrystals on top of polyelectrolyte-polymers based on photogenerated potential buildup where no external bias is applied.